2014
DOI: 10.1002/eji.201344383
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal phospholipase A2: A novel player in host immunity to Mycobacterium tuberculosis

Abstract: Phospholipases catalyze the cleavage of membrane phospholipids into smaller bioactive molecules. The lysosomal phospholipase A 2 (LPLA 2 ) is specifically expressed in macrophages. LPLA 2 gene deletion in mice causes lysosomal phospholipid accumulation in tissue macrophages leading to phospholipidosis. This phenotype becomes most prominent in alveolar macrophages where LPLA 2 contributes to surfactant phospholipid degradation. High expression of LPLA 2 in alveolar macrophages prompted us to investigate its rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…While bacterial phospholipases can be detrimental to the host, conversely, host phospholipase activities can antagonize the survival of intracellular pathogens. In the context of mycobacterial infections, host phospholipase D and lysosomal phospholipase A2 have been implicated in the cells’ ability to control intracellular mycobacterial growth ( 94 , 95 ). It should be noted that these studies were focused on the enzymes, and the exact lipid mediators remain to be identified.…”
Section: Host Lipids—the Protagonist and The Antagonist In The Macropmentioning
confidence: 99%
“…While bacterial phospholipases can be detrimental to the host, conversely, host phospholipase activities can antagonize the survival of intracellular pathogens. In the context of mycobacterial infections, host phospholipase D and lysosomal phospholipase A2 have been implicated in the cells’ ability to control intracellular mycobacterial growth ( 94 , 95 ). It should be noted that these studies were focused on the enzymes, and the exact lipid mediators remain to be identified.…”
Section: Host Lipids—the Protagonist and The Antagonist In The Macropmentioning
confidence: 99%
“…Genetic deletion of LPLA 2 results in unusual accumulation of non-degraded lung surfactant phospholipids in lysosomes of alveolar macrophages, leading to phospholipidosis, 80 ) perturbed presentation of endogenous lysophospholipid antigens to CD1d by invariant natural killer T (iNKT) cells, 81 ) and impairment of adaptive T cell immunity against mycobacterium. 82 )…”
Section: Lipoquality Control By Intracellular Pla 2 mentioning
confidence: 99%
“…LPLA2 is ubiquitously expressed but is most abundant in terminally differentiated alveolar macrophages 3 and is important for lung surfactant metabolism 4 and maturation of invariant natural killer T cells 5 . Inhibition of LPLA2 might be responsible for cellular toxicities caused by the administration of cationic amphiphilic drugs such as amiodarone 6 , and recent studies on LPLA2 knockout mice have linked LPLA2 to lupus erythematosus 1 and the innate immune response to infection by mycobacteria 7 . LCAT, 50% identical in amino acid sequence to LPLA2, associates with high and low density lipoprotein (HDL and LDL) particles in plasma and catalyzes an essential step in reverse cholesterol transport from peripheral tissues to the liver 8 .…”
mentioning
confidence: 99%